The Utilization of Picture Puzzle Media to Enhance Arabic Vocabulary Mastery at Madrasah Ibtidaiyah Bandar Lampung - Dani Saputra; Sulthan Syahril; Irwandani (Language, Technology, and Social Media, 2024)
This study aims to implement and explore the use of pictorial puzzle media in enhancing students' Arabic vocabulary mastery. The method used in this study is Classroom Action Research (CAR), conducted in 2 cycles, with each stage consisting of four steps: planning, implementation, observation, and reflection. The research instruments used were student observation sheets and test results. From the preliminary study conducted on 13 students, only 3 students achieved the minimum mastery criteria, while 10 students did not, with an average score of only 69.7, whereas the minimum mastery criteria at Madrasah Nurul Hikmah is 75, indicating that the students' scores were still below the minimum mastery criteria. The research results after implementing pictorial puzzle media showed an increase in the Arabic vocabulary mastery of class V students at Madrasah Nurul Hikmah Bandar Lampung. This was evidenced by the increase in the average scores of students, which rose from 69.7 in the pre-cycle to 74.6 in cycle I and 88.5 in cycle II. The regular use of pictorial puzzle media can enhance students' ability to master Arabic vocabulary. This indicates that this method can be an effective solution for improving Arabic language learning in Madrasahs, and provides evidence that using visual approaches can greatly aid in improving students' learning outcomes.